Some Reflections on Graduate Professional Education in Adult Education - Verner, Coolie (Canadian Journal of Higher Education, 1978)
Adult education is a relatively new discipline that is appearing with greater frequency in university curriculae. Although Columbia University established the first department in 1930 proliferation has been slow and by 1962 some fifteen universities had established departments1. Among these, were some of the most noted universities on the continent. Well over 100 universities and colleges now purport to offer graduate professional education in adult education but it is doubtful that all of these are in fact legitimate programs in adult education.